REVITALISASI AGAMA DI SULUT(KASUS STUDI KELOMPOK ALIRAN SYIAH DI MANADO) - Ali Amin (Institut Agama Islam Negeri (IAIN) Manado, 2017)
Abstract. This study discusses the social history and development of Shiite groups in Manado. It is known in Manado that there are Shi'ite religious groups with various organizations. This study wants to answer the question: how come and the development of Shi'ite followers in Manado. Start when it comes and develops. Who are the characters, and how they relate to similar flow groups in Indonesia. Through the method of observation and in-depth interviews with various parties involved in Manado and surrounding areas, this research found several important things including: the understanding or ideological thinking of the Shi'a sect has basically been accepted since the development of Islamic activism which was rolled out after the 1979 Iranian revolution. became a religious organization along with the opening of the taps of political reform in Indonesia, precisely in 2005 when the Shiite-based study groups began to develop in Manado. The acceptance of this group is mainly due to emotional closeness both in terms of kinship or other social relations between the group figures and their followers. The acceptance of this group is also due to the phenomenon of